Two-Parameter Regularization Method for a Nonlinear Backward Heat Problem with a Conformable Derivative. (5th May 2020) - Ho, Vu; O'Regan, Donal; Van, Hoa Ngo
Abstract : In this paper, we consider the nonlinear inverse-time heat problem with a conformable derivative concerning the time variable. This problem is severely ill posed. A new method on the modified integral equation based on two regularization parameters is proposed to regularize this problem. Numerical results are presented to illustrate the efficiency of the proposed method.